Inhibition effect of hydrocolloid irreversible alginate on soaking spray using aloe vera juice - Dedi Sumantri; Chaira Maulida (DiscoverSys Inc., 2018)
Introduction: Alginate impression material is the most commonly used in dentistry to get a negative mold of the oral tissues. Alginate impression material has imbibition effect when in contact with the liquid during the disinfection process. This study aimed to observe the imbibition effect on alginate impression material soaked and sprayed using Aloe vera juice.Methods: The research method used was a laboratory experimental with pretest and posttest. Alginate was molded by using a mold with the size of 28 mm in diameter and 18 mm high. The results of molding alginate were soaked and sprayed using Aloe vera juice 100% for 5 minutes and 10 minutes. Calculation of imbibition was performed by weighing using digital scales. The normality tested by Shapiro-Wilk and the data were analyzed by Mann Whitney.Result: The results showed that there were imbibition effects on alginate molding soaked and sprayed for 5 minutes and 10 minutes, the test indicated that there were significant differences (p<0.05) between 10 minutes and 5 minutes soaking. Meanwhile, between 5 minutes and 10 minutes spraying, no significant difference was obtained (p>0.05).Conclusion: This study concludes that it occurs the smallest imbibition effect on a spraying treatment using Aloe vera 100% for five minutes.